Neo-Extractivism in Latin America – one side of a new phase of global capitalist dynamics (2016)
The aim of this text is to make sense of the emerging political-institutional, territorial, and socio-ecological dynamics and contradictions of neo-extractivism in Latin America in the context of global capitalist development. In contrast to some existing literature, we argue that the term ‘neo-extractivism’ should not be restricted to countries with progressive governments but be applied to all Latin American societies that, since the 1970s and especially since the year 2000, depend predominantly on the exploitation and exportation of nature. We argue that the often vague usage of the term neo-extractivism can be strengthened when it is seen in line with dominant development models. Therefore we refer to regulation theory and its historical heuristic of different phases of capitalist development. This enables us to look at the temporal-spatial interdependencies between shifting socio-economic and technological developments, world market structures, and political-institutional configurations that characterize neo-extractivism across scales and beyond national borders.